CONTRIBUTIONS OF CASSAVA ENTERPRISE TO SOCIO-ECONOMIC STATUS OF ENTREPRENEURS IN SOUTH-EASTERN NIGERIA (2014)
Cassava, being an important staple, is widely grown in Nigeria. Potential contribution of Cassava Enterprise (CE) to Socioeconomic Status (SES) of entrepreneurs is threatened by fluctuation and unpredictability of cassava production, processing and marketing activities. Information on contributions of CE to entrepreneurs' SES is scanty. Therefore, contributions of CE to entrepreneurs' SES in south-eastern Nigeria were investigated. Multistage sampling procedure was used to select respondents for the study. Imo and Anambra states were selected from five south-eastern states of Nigeria due to high involvement in CE. Systematic sampling procedure was used to randomly select 20% of registered cassava producers (81, 54), processors (51, 36) and marketers (50, 36) groups from Imo and Anambra states respectively resulting in 308 entrepreneurs. Interview schedule was used to collect data on respondents' personal characteristics, enterprise characteristics, extent of involvement in CE, benefits derived and constraints to involvement in CE. Indices of benefits (0-57.5 is low, 57.6-74.9 is moderate and 75-77 is high), involvement (2-4.8 is low, 4.9-10 is high) and SES (110-154.07 is low, 154.08-168.16 is moderate and 168.17-169 is high) were generated for analysis. Data were analysed using descriptive statistics, ANOVA and regression analysis at p = 0.05. Annual income, age and years of experience in CE were N24965.1'75.59, 55.69'6.792 and 36.78'9.942 respectively. Most respondents were females (77.9%), married (95.8%) and had formal education (67.2%). Most entrepreneurs (83.4%) were highly (4.9'1.6) involved in CE. Most producers of fresh tubers (87.4%) and stem cuttings (76.1%) operated on small scale of 309.1'358.4 bags/season and 259.6'289.6 bundles respectively. Garri (97.7%) and fufu (98.8%) were processed at small scale of 81.9'20.6 and 46.4'26.1 bags/season respectively. Stem cuttings (85.1%) fresh tubers (96.6%), fufu (97.6%) and garri (97.7%) were marketed at small scale of 192.3'91.6 bundles, 745.2'96.9, 88.1'10.3 and 89.7'24.9 bags/season respectively. Major constraints of entrepreneurs were lack of credit (93.8%) and technical knowledge (96.1%). Food security (92.6%), improved diet (73.7%) and recognition in the society (85.7%) were major benefits derived by entrepreneurs. Producers (67.3'8.7) and marketers (67.2'7.4) had higher benefits from CE than processors (63.7'9.5) but it was not significant. The SES for marketers (162.8'3.1), producers (161.0'7.2) and processors (159.7'8.8) were essentially moderate. Experience (? = 2.638), benefits derived (? = 3.247) and income (? = 3.103) significantly increased producers' SES. Marketers' SES was significantly increased by constraints (? = - 3.248) and benefits derived (? = 3.279). Processors' SES was significantly enhanced by income (? =3.120), years of experience (? = 2.095), and benefits (? = 5.867). Income and benefits derived from cassava enterprise were the two major factors that enhanced the socio-economic status of the entrepreneurs.